Design and implementation of voltage regulator for a power supply - Tay, Edwin Jun Kiat (Nanyang Technological University, 2021)
Voltage regulator is used to obtain a constant desirable output voltage which is essential in our daily life now. With the continuous advancement of technology and complexity of circuit designs, it has shown that voltage regulator is a very important component to regulate the output voltage in order not to damage or overheat any other electronic components and/or devices. This report displays the knowledge and learning experience gained throughout the duration of the final year project. The learning process includes the designing of the selected types of voltage regulators for power supply and the implementation of them. This project mainly focused on researching, software simulation, circuit implementation and the comparison between simulated and theoretical results. There are two types of voltage regulators, linear regulators and switching regulators. Zener shunt, transistor shunt, transistor series, fixed and variable voltage regulators are being focused as the selected linear regulators. Buck converter, boost converter and buck-boost converter are the selected switching voltage regulators. The two software used in this project are MultiSim and LTspice XVII to design and simulate the circuits to obtain the results of the design. The hardware implementation of this part is to solder the components onto a printed circuit board (PCB). Then a comparison between the PCB and breadboard will be done and analyse the results obtained from both.